COMPREHENDING DISASTER RISK MANAGEMENT STRATEGIES: A REVIEW OF BUILD BACK BETTER AND BUILD BETTER BEFORE - Shah, Ali Ahmed; Mohamed Zaid, Suzaini; Anak Tedong, Peter Aning (Journal of Surveying, Construction and Property, 2025)
The rising frequency and intensity of climate emergencies, coupled with their amplified disaster impacts, result in substantial human and economic costs. There is a deficiency in effective strategies for disaster risk management to address this destructive phenomenon. The effectiveness of Build Back Better (BBB) remains uncertain, exhibiting limitations in its implementation, especially in developing and least developed countries characterized by unique socioeconomic and societal vulnerabilities. Research on the concept of Build Better Before (BBBf) is limited, and its potential to address deficiencies in disaster risk management in underdeveloped contexts is scarce. Therefore, there is an urgency to investigate the effectiveness and applicability of these approaches and highlight the optimal option for specific contexts. The study conducted a systematic literature review following PRISMA guidelines to achieve this objective. Fourty papers were analysed regarding BBB and BBBf in recent literature (2017-2024). The literature suggests that the BBBf approach presents a viable alternative with various comparative advantages, including economic efficiency, support for bottom-up approaches, and increased involvement of local governments. The emphasis on community resilience and costeffectiveness in the BBBf initiative enhances its viability for community adoption, promoting long-term sustainability, especially in contexts characterized by financial challenges, societal vulnerabilities, and governance complexities.